Nonspecific interactions in biomedical applications. (June 2020) - Adibnia, Vahid; Mirbagheri, Marziye; Salimi, Sina; De Crescenzo, Gregory; Banquy, Xavier
Abstract: Nonspecific interactions play a major role in the microscale functioning of biological units. Exploiting these interactions in design and application of biomedical systems has been beneficial in different branches of biomedicine. In this review, recently designed biomedical systems that function mainly, or partially, based on nonspecific interactions, including but not limited to electrostatic, hydrophobic, and steric interactions, are discussed. The focus will be on the application of these interactions in biolubrication, bioadhesion and antifouling, drug delivery, and tissue engineering. The information gathered in this review can be helpful in guiding the readers in the direction that the field has been following in the past few years. Graphical abstract: Image 1